2013
DOI: 10.1007/s00216-013-7418-8
|View full text |Cite|
|
Sign up to set email alerts
|

Stability and efficiency of supported liquid membranes in electromembrane extraction—a link to solvent properties

Abstract: The current work presents a large systematic screening of 61 possible organic solvents used as supported liquid membranes (SLM) in electromembrane extraction (EME). For each organic solvent, recovery, current across the SLM, and stability considerations have been investigated and correlated to relevant solvent properties through partial least square regression analysis. The five unpolar basic drugs pethidine, haloperidol, methadone, nortriptyline, and loperamide were used as model analytes. Efficient EME solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In relation to the theory discussed in Section , the pH changes alter the distribution coefficients included in the equations. Drop in recovery due to long extraction times has also been explained by partial degradation of the liquid membrane, either by dissolution into the sample or by water penetration into the liquid membrane .…”
Section: Mass Transfer In Eme From An Experimental Point Of Viewmentioning
confidence: 99%
“…In relation to the theory discussed in Section , the pH changes alter the distribution coefficients included in the equations. Drop in recovery due to long extraction times has also been explained by partial degradation of the liquid membrane, either by dissolution into the sample or by water penetration into the liquid membrane .…”
Section: Mass Transfer In Eme From An Experimental Point Of Viewmentioning
confidence: 99%
“…Later, the magnitude of the released heat was found to be insufficient to cause severe problems [23]. Another factor attributed to the performance loss is the propagation of double layer capacitance caused by the ambulation of charged species on both sides of the SLM [24]. Kuban and coworkers introduced another limiting feature of EME.…”
Section: Introductionmentioning
confidence: 98%
“…While the main driving force of the extraction in EME is the applied voltage, the overincreasing of voltage results in loss of recovery and instability problems [28]. It has been reported that the mass transfer resistance, double layer capacitance, increased current and bubble formation are responsible for the above problems [24,29]. Generally, pH of donor/acceptor solution is adjusted to keep the analyte in its ionized form [30] and to make a pH gradient between the two phases [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, tris(2-ethylhexyl) phosphate (TEHP) has been used as an non-ionic carrier [27]. TEHP is expected to improve mass transfer of polar basic drugs based on dipole and hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Non-polar basic drugs in their protonated form are easily transferred into the SLM under the influence of an electrical field, based on strong dipole and hydrogen bonding interactions with NPOE [27]. On the other hand, EME of polar basic drugs (log P < 2) is more challenging due to their low affinity to the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 relatively high extraction recoveries have been reported with DEHP [31], this carrier increase the electrical conductance of the SLM, and also facilitate transfer of back-ground electrolyte ions and sample matrix ions across the SLM.…”
Section: Introductionmentioning
confidence: 99%